1965
DOI: 10.2172/1073028
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Rocket Program, Metallurgy Division progress report for quarter ending December 31, 1964

Abstract: A. Cladding Requirements 7B. Pressure Bonding 71. Autoclave Testing 72. Thermocouple Failures 77 3. Bonding Tests 79 VII. Properties of High-Temperature Materials. 8l A. Properties and Materials Considered 82 B. Young' s Modulus of Unalloyed Tungsten 82 C. Young*s Modulus of Tungsten-25w/o Rhenium 85

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Burt et al [8] obtained a different result (greater fuel loss) as the effect of W coating on UO 2 particles for a W-25 vol.% UO 2 cermet. The researchers believed that the increased UO 2 loss with W coating on UO 2 was a result of fracture caused by thermal expansion mismatch between UO 2 and the W coating.…”
Section: Fabrication Condition Effectsmentioning
confidence: 97%
See 4 more Smart Citations
“…Burt et al [8] obtained a different result (greater fuel loss) as the effect of W coating on UO 2 particles for a W-25 vol.% UO 2 cermet. The researchers believed that the increased UO 2 loss with W coating on UO 2 was a result of fracture caused by thermal expansion mismatch between UO 2 and the W coating.…”
Section: Fabrication Condition Effectsmentioning
confidence: 97%
“…The authors stated, however, that the appearance of the coprecipitated powders indicated probable impurity contamination. Burt et al [8] also showed results in which cermets containing coarser particles gave better UO 2 loss performance; under thermal cycling at 2460°C in H 2 , W-50 vol.% UO 2 that contained 'micronized' (smaller) UO 2 particle sizes failed more quickly than a cermet containing 'ceramic grade' (larger) particle sizes. No explanation was given for the particle-size effect.…”
Section: Fabrication Condition Effectsmentioning
confidence: 97%
See 3 more Smart Citations